2020
DOI: 10.1016/j.xphs.2019.10.063
|View full text |Cite
|
Sign up to set email alerts
|

Algorithm-Based Liquid Formulation Development Including a DoE Concept Predicts Long-Term Viral Vector Stability

Abstract: Specifically tailored amino acidebased formulations were previously shown to have a high potential to avoid stress-mediated degradation of complex molecules such as monoclonal antibodies and viral vectors. By using adenovirus 5 (Ad5) as a model, we studied whether such formulations may also efficiently protect viral vectors in thermal stress experiments and during long-term liquid storage. Algorithm-based amino acid preselection using an excipient database and subsequent application of design of experiments (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…138 Isomerization is prevalent in AAV viral vectors and has been reported in AAV5 under various stress conditions. 139…”
Section: Isomerizationmentioning
confidence: 99%
See 2 more Smart Citations
“…138 Isomerization is prevalent in AAV viral vectors and has been reported in AAV5 under various stress conditions. 139…”
Section: Isomerizationmentioning
confidence: 99%
“…98 are susceptible to oxidation. Capsid proteins can oxidize upon exposure to light and due to metal ion impurities in the raw materials and excipients, 139 leading to a loss in functionality. 136 Oxidation can be prevented with the use of free amino acids such as methionine and histidine and metal ion scavengers such as ethanol, EDTA and DTPA.…”
Section: Free Radical Scavengersmentioning
confidence: 99%
See 1 more Smart Citation
“…They have recently published and extensively patented methods using algorithmic methods to identify mixtures of excipients which can stabilize diverse types of biopharmaceuticals. With this method they used Design of Experiments principles combined with accelerated stability testing to determine mixtures of excipients which most effectively preserved the stability of adenoviral vectors [ 186 , 187 ]. It remains to be seen what degree of stability this method may be able to impart to a vector-based vaccine against SARS-CoV-2.…”
Section: Viral and Vector Based Formulationsmentioning
confidence: 99%
“…30 Reinauer et al (2020) used a DoE approach with iterative optimization rounds and they reported significant enhancement of the stability of liquid, adenoviral vector vaccine formulations following such an algorithm. 31…”
Section: Optimizing Stability Of Liquid Formulationsmentioning
confidence: 99%